Revolutionizing Zakat Philanthropy: Strategic Digital Fundraising Empowered by SOAR Analysis at Ulil Albab Institution - Nasution, Amalia; Syahbudi, Muhammad; Harahap, Muhammad Ikhsan (IAIN Manado, 2025)
This study aims to analyze digital fundraising strategies in the collection of zakat funds at Ulil Albab Amil Zakat Institution (LAZ), employing the SOAR framework (Strengths, Opportunities, Aspirations, Results). Utilizing a descriptive research method paired with a quantitative approach, the SOAR analysis is quantitatively developed through surveys conducted with five informants (n=5). The data are weighted and rated on a scale from 1 to 4, adapted from the IFE and EFE models. The results indicate that Strengths scored 1.75, Opportunities 1.83, Aspirations 2.04, and Results 1.40, totaling 7.01 overall. Quadrant mapping produced the highest score in the OA combination at 3.87, followed by SA at 3.79, OR at 3.23, and SR at 3.15. These findings demonstrate that OA was selected as the main strategic priority due to its dominant score. This strategy highlights the utilization of external opportunities, such as the rise of digital zakat trends, increased technological literacy within society, and the availability of online payment infrastructure, complemented by the internal aspiration of LAZ Ulil Albab to enhance accountability, transparency, and the institution’s digital positioning. The resulting strategy incorporates real-time digital reporting, technological innovation through the integration of e-wallets and payment gateways, digital education-oriented branding reinforcement, and the development of human resource capacity and partnerships. The study confirms that the OA strategy is effective in boosting zakat fundraising, strengthening donor trust, and supporting institutional sustainability over the long term.